Effects of exercise training on the cardiovascular system: Pharmacological approaches - Zanesco, Angelina; Antunes, Edson (Elsevier B.V., 2007)
Physical exercise promotes beneficial health effects by preventing or reducing the deleterious effects of pathological conditions, such as arterial hypertension, coronary artery disease, atherosclerosis, diabetes mellitus, osteoporosis, Parkinson's disease, and Alzheimer disease. Human movement studies are becoming an emerging science in the epidemiological area and public health. A great number of studies have shown that exercise training, in general, reduces sympathetic activity and/or increases parasympathetic tonus either in human or laboratory animals. Alterations in autonomic nervous system have been correlated with reduction in heart rate (resting bradycardia) and blood pressure, either in normotensive or hypertensive subjects. However, the underlying mechanisms by which physical exercise produce bradycardia and reduces blood pressure has not been fully understood. Pharmacological studies have particularly contributed to the comprehension of the role of receptor and transduction signaling pathways on the heart and blood vessels in response to exercise training. This review summarizes and examines the data from studies using animal models and human to determine the effect of exercise training on the cardiovascular system. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: exercise training; adrenergic receptors; muscarinic receptor; nitric oxide; cardiac tissues; vascular smooth muscle